2023
DOI: 10.1002/mop.33638
|View full text |Cite
|
Sign up to set email alerts
|

A single‐layer differential‐fed dual‐band filtering antenna for WLAN application

Abstract: In this letter, a single‐layer differential‐fed dual‐band filtering antenna for wireless local area network application is proposed. The proposed antenna consists of a square patch, and two pairs of stepped impedance resonators (SIRs). The lower operating passband is realized by exciting the square patch with a pair of differential ports. Then, a pair of SIRs is connected with the radiating edge of the square patch to introduce another resonance, thus forming the upper passband. And a radiation null is simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The impedances of differential antennas can be calculated systematically in terms of the two-port network parameters. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In the studies by Tu and colleagues, 12,13 the analysis of the impedance relationship of a rectangular patch antenna with a differential feed is provided. The impedance of differential antenna for both differential and common modes can be characterized by measuring associated scattering parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impedances of differential antennas can be calculated systematically in terms of the two-port network parameters. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In the studies by Tu and colleagues, 12,13 the analysis of the impedance relationship of a rectangular patch antenna with a differential feed is provided. The impedance of differential antenna for both differential and common modes can be characterized by measuring associated scattering parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Since practical antennas are low loss, the BCITL can be effectively employed to model low-loss antennas to understand physical mechanisms better. It will be shown that the novel BCITL model can simplify impedance relationships for differential microstrip antennas, compared to the previously published methods based on the two-port network parameters, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] with accurate results and better physical insights. To validate the proposed model, simulation, and measurement results are compared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots organization and school use network computer for finish work they. Suite incident This has increase request customer will quality network Good in LAN nor WAN [1]. Quality network computer can solve the problem transfer information which slow, the need for data exchange in each section and real-time transactions, with the existence of a computer network that is connected to each work unit on an ongoing basis no direct can increase efficiency work and can improve data processing in an organization [2].…”
Section: Introductionmentioning
confidence: 99%
“…Need current information must be realtime to be able to speed up data processing which can produce information needed by the network computer, especially need fast transfer of data, effective and efficient. With an integrated computer network between one user and another, it can improve the performance of an institution, especially schools which are currently implementing an online learning model [1].…”
Section: Introductionmentioning
confidence: 99%